Mathematic modeling of farmer household income in Singosari Village, Tanggamus District - Ariyanto, Komang (Jurusan Matematika FMIPA Universitas Jember, 2023)
Farmers engage in various sectors (agriculture and non-agriculture) to earn income in order to meet their diverse household needs. Based on various pieces of literature, the agricultural sector serves as a gauge for the income level of rural farming households and provides a greater contribution than the non-agricultural sector. The purpose of this research is to analyze the mathematical modeling of household income among farmer households and to assess the contribution of the agricultural sector to households in Singosari Village, Tanggamus Regency. This study employs a quantitative method with a case study approach. The population in this study consisted of 464 heads of households, from which a sample of 30 households was selected. The respondents in this study were farmer households, and data were collected through surveys using questionnaires, documentation, and literature studies related to the mathematical modeling of income and the contribution of the agricultural sector to people's livelihoods. Data processing was conducted using SPSS software version 26, assisted by Microsoft Excel, and data analysis was performed using a simple linear regression model. The findings of this study indicate that, in Singosari Village, the agricultural income variable significantly influences the household income variable, as determined from the significance value of the simple linear regression results.Keywords: Agricultural income, household income, mathematical modeling, simple linear regression, singosari farmersMSC2020: 62P25